Im Schmelztiegel der Kulturen. Zum Band Transkulturelle Durchdringungen in der Gegenwartsliteratur Mitteleuropas - Sidowska, Karolina (Zagadnienia Rodzajów Literackich, 2022)
The main theme of the essay is the phenomenon of intercultural relations as revealed in contemporary literature from Central Europe. The point of reference is a monograph containing several articles on the subject. The overarching category for all texts is transculturalism (in the sense of W. Welsch), a term which, like Central Europe, is subjected to critical reflection by the author. In addition, issues of migration and border-crossing, both geographically and existentially, discrimination and the experience of alienation, problems of defining one’s own identity, are the focus of attention. In a particular way, these issues relate to border areas in habited by representatives of different nationalities, many of which can be found in Central Europe (e.g., Cieszyn Silesia), but also to specific historical moments in which cultural clashes were violent and led to trauma (World War II, the Holocaust). Among the literature cited are works by Ramona Ambs, Olga Grjasnowa, Marina Frenk, Andrzej Stasiuk, Paweł Huelle, Gustaw Morcinek, Edith Schmettan-Demel et al. A separate point of interest is literature as a medium for intercultural understanding. Not only translations and the international reception of literary works, as well as intertextual inspirations and references (e.g., the reception of Thomas Bernhard’s work in contemporary Polish prose), but also certain developmental similarities and thematic convergences in different national literatures are relevant in this context.